FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN DENGAN PEMODERASI KOMITMEN ORGANISASI (Studi Pada Badan Pusat Statistik Se-Provinsi Banten) - Yanto, Triyanto (Pascasarjana Universitas Sultan Ageng Tirtayas, 2019)
The purpose of this study is to analyze the factors that affect the quality of financial statements by moderating organizational commitment at the Central Bureau of Statistics of Banten Province. The population of this study is financial managers who have the duties and responsibilities in financial management that directly or indirectly affect the quality of financial reports in the 9 work units of the Banten Provincial Statistics Agency. Data collection by distributing 70 questionnaires to financial managers. The sampling technique uses a census method in which the entire study population is used as the research sample. The method of data analysis was done by PLS SEM with the help of the Smart PLS program. The results of this study prove that the implementatition of accrual-based goverment accounting standards, the use of information technology has a significant positive effect on the quality of financial statements while the understanding of accounting and the role of internal audit does not affect the quality of financial statements. Organizational commitment as a moderating variable is not able to moderate the influence of the application of accrual-based accounting standards, understanding accounting, utilization of information technology and the role of internal audit on the quality of financial statements.